Activity of the combined pyrimethamine and sulphadoxine as antifilarial in Brugia pahangi - Aedes togoi model infection - Sugeng Juwono Mardihusodo, Sugeng Juwono Mardihusodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
The mortality rates of Aedes togoi mosquito either uninfected or infected with Brugia pahangi maintained in insectary for 12 days with various concentrations of the combined pyrimethamine (P) and sulphadoxine (S) in 10% sugar-water solution: 5 mg% P + 100 mg%, 10 mg% P + 200 mg% S, and 20 mg% P + 400 mg% S significantly increased compared to that of the control groups. The present evidence showed a definite insecticidal action of the combined drugs.Infection and infective rates of Ae. togoi mosquitoes, average number of B. pahangi larvae and infective larvae per infected mosquitoes, average size and movement of the larvae in the groups of mosquitoes treated with various concentrations of the combined drugs for 12 days decreased significantly compared to that of the control groups of mosquitoes. The present evidence demonstrated a definite action of the combined pyrimethamine and sulphadoxine as an antifilarial in B. pahangi Ae. togoi model infection.Key Words: pyrimethamin-sulphadoxine - Brugia pahangi - Aedes togoi - antifilarial - insecticide